Repeated Successful Nest Sharing and Cooperation Between Western Kingbirds (Tyrannus verticalis) and a Female Western Kingbird × Scissor‐Tailed Flycatcher (T. forficatus) Hybrid - Alexander J. Worm; Emily R. Donahue; Than J. Boves; Andrew D. Sweet (Ecology and Evolution)
ABSTRACT Nest sharing by birds, or the phenomenon where multiple individuals of different species contribute genetically and parentally to offspring in a single nest, is a rare form of cooperative breeding that has only occasionally been reported in socially monogamous birds. Here we describe, both behaviorally and genetically, the unique case of two female birds, a western kingbird (Tyrannus verticalis) and a western kingbird × scissor‐tailed flycatcher (T. forficatus) hybrid, simultaneously occupying (and likely co‐incubating eggs in) a single nest. Both females provisioned nestlings, and they did this in two consecutive years (producing four fledglings each year). Genomic data from the females revealed that they were unrelated, and parentage analyses revealed that both females contributed genetically to at least one of the offspring, and at least two fathers were involved. These observations represent the first reported case of nest sharing involving a hybrid individual and the first case within the family Tyrannidae.